Computational simulation including interpretation of the importance of the immune system in tumor growth - et. al., Nidhi S Vaishnaw, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The secret to tumor growth and survival is proliferation. Therefore, to plan and formulate a required therapy process, the study of the propagation rate is very important. The objective of the immune system is to protect against disease or other potentially harmful foreign bodies, a set of processes and mechanisms within the body. In regulating the growth of a tumor, different cells of our immune system perform their assigned function. Natural Killer cells, Dendritic cells, and CD8+ cells are among the many cells. In our scientific literature, in the presence of numerous family components of the human immune system, we have developed a mathematical model to evaluate the dynamics involved in tumor formation. We separated the population of tumor cells into proliferating and inactive subsets and felt that the cells of the immune system had little effect on the dormant cells. This partition of the universal tumor set into the subsets as mentioned has never been made in any of the previous research works. Also, to the best of authors’ knowledge, the compartment combination considered for the present work adds novelty to the article.